Benefits of Treatment Completion Over Premature Termination: Findings from the National Child Traumatic Stress Network. Issue 2 (3rd April 2019) - Steinberg, Alan M.; Layne, Christopher M.; Briggs, Ernestine C.; Liang, Li-Jung; Brymer, Melissa J.; Belin, Thomas R.; Fairbank, John A.; Pynoos, Robert S.
Abstract : Objective : To evaluate potential differences in therapeutic outcomes between youths who completed a full course of treatment as planned compared to youths who terminated treatment prematurely. Method : Using longitudinal data from the National Child Traumatic Stress Network (NCTSN) Core Data Set, the present study examined demographic characteristics, trauma history, scores on standardized measures, and ratings of functional impairment and behavior problems in a large clinical sample of children and adolescents exposed to trauma who received treatment at NCTSN centers across the United States. Baseline and follow-up data were used to compare treatment completers ( n = 3, 108) and noncompleters ( n = 4, 029). Results : Both treatment completers and noncompleters received benefits from treatment by NCTSN mental health providers in that both groups showed significant decreases in mean scores from baseline to follow-up on all standardized measures. However, compared to noncompleters, treatment completers showed three types of significantly greater benefit at follow-up. These included: (a) greater rates of decline (i.e., steeper slopes) on all outcome measures; (b) greater reductions in the odds of falling within the clinical range on standardized measures; and (c) greater reductions in the odds of exhibiting functional impairment and behavior problems at follow-up. In contrast, compared to treatment completers, noncompleters reported significantly higher rates of lifetime exposure to community violence, psychological maltreatment, physical abuse, neglect, sexual abuse, and sexual assault. Conclusion : These findings underscore the value of incorporating engagement and retention strategies in treatments for traumatized youths to maximize therapeutic benefit and raise the standard of care.